Prevalence and associated risk factors of soil-transmitted helminths among refugee children in the Klang Valley, Malaysia - Alaribi, Alhamil Fatma Ibrahem (2020)
Objectives: The main objective of this study is to investigate the prevalence of soil-transmitted helminths (STHs) among refugee children in selected areas in the Klang Valley, and determine its associated risk factors and complications. Methodology: This is a cross-sectional study carried out over two years from (February) 2017 to (September) 2019. Tools for the study included a survey questionnaire on socio-demographic profiles of the survey respondents, hygiene practice and clinical manifestations, anthropometric measurements, anaemia determination by HemoCue and determination of the infection by direct microscopy from fecal samples. Results: The prevalence of STHs infestation in this study population was 37.2 % and the infection was associated with i.e. being a Rohingya (p = 0.001), those with low monthly income parents (p = 0.001), those with not-working fathers (p = 0.01), living in flats (p = 0.013), low levels of parent’s education (father; p = 0.043, mother; p = 0.013), with only one toilet in the house (p = 0.03), had previous history of worm infection (p = 0.01), had pallor (p = 0.006), and anaemia (0.001). Regression analysis showed Rohingyan (19.93), those with non-working fathers (8.36), parents with low monthly income (2.38), those with history of worm infection (3.35) are more likely to be infected. Complications like anaemia were high i.e. with prevalence of 37.8 %. It was found that respondents who have STHs infection i.e. 3.67 are more likely to have anaemia (p < 0.05). In addition, anthropometric measurements found 12.2 % of respondents were undernourished. Conclusion: The evidence from this study suggested that proper and strategic intervention should be conducted among the refugee community to reduce morbidity due to STHs infection. An alternative and efficient system to provide the refugee schoolchildren with basic care for sanitation and health provision is needed. A voluntary clinic provided by non-government organisations is recommended to focus on counselling and advice on personal hygiene of the children.